Ultrathin wide-bandgap niobate for high-performance photodetection and information encryption - Xiaoqiang Feng; Xiaolin Zhang; Ran Liu; Xiaolong Guo; Yuchan Hu; Lizhikun Gong; Yiling Yu; Lei Yin; Yao Wen; Yuchen Cai; Ruiqing Cheng; Jun He (Science Bulletin, 2026)

Direct functional recycling of waste polyester-cotton blended textiles into photothermal materials for solar-driven water evaporation and anti-icing/de-icing - Zijun Feng; Lan Bai; Jing Yu; Wenhao Xu; Chengfeng Shen; Yifan Liu; Yiling Wu; Shimei Xu; Yuzhong Wang (Chemical Engineering Journal, 2026)

On-site evolution of bifunctional NiCoP nanosheet electrode for electrocatalytic co-produce acetate and hydrogen from ethanol - Nanjia Yang; Yongsheng Wang; Yanan Chen; Yizhen Li; Jiansheng Wang; Chuanyi Zhang; Kaifeng Wang; Yiling Feng; Yuxin Zhu; Wei Zhu; Zhongbin Zhuang (Chemical Engineering Journal, 2026)

Efficient and stable membrane fouling control in MFC-MBR system facilitated by conductive membrane electrodes - Xiao Zhu; Yiling Gu; Nan Jiang; Jiaping Wu; Wenxin Chen; Suhao Feng; Ding Huang; Jianmao Yang; Manhong Huang (Journal of Water Process Engineering, 2026)

Oligomer production and effects on gut microbiota of PLA and PBAT biodegradable microplastics in in vitro digestion model - Guowei Ma; Xiaomeng Gao; Zhihui Li; Yuting Chen; Hanfei Li; Yiling Cui; Peixue Guo; Biao Yang; Di Feng; Tingting Zhao (Food Bioscience, 2026)

Deficiency of primate-specific TFDP3 causes male infertility with oligoasthenoteratozoospermia in humans and cynomolgus monkeys - Chunyu Liu; Chaofeng Tu; Peng Li; Huan Wu; Feng Wan; Yong Lu; Shuyan Tang; Xin Li; Kuokuo Li; Jiaxiong Wang; Yang Gao; Xinyan Geng; et al. (Science China Life Sciences, 2026)

Environmental stress-stable bigels structured by sitosterol–oryzanol and guar gum: Dual-network mechanism and food-relevant applications - Lijuan Han; Yiling Xu; Shiqi Zhang; Mengyuan Xie; Yifeng Han; Hailong Zhang; Chun Hu; Jiangtao Feng (Food Hydrocolloids, 2026)

Uncrossing the ‘X’: Characterization of alternative alleles for KSLX in Oryza - Tristan Weers; Yiling Feng; Reuben J. Peters (Phytochemistry, 2025)

Non-targeted identification and risk classification for chemical migrants in 41 disposable biodegradable tableware - Yuting Chen; Xiaomeng Gao; Guowei Ma; Liqian Wang; Peixue Guo; Yiling Cui; Jingwei Zhang; Di Feng (Food Bioscience, 2025)

Chemical migration, digestive behaviors and effect on gut microbiota of PLA and PBAT oligomers - Guowei Ma; Xiaomeng Gao; Yuting Chen; Hanfei Li; Yiling Cui; Peixue Guo; Tingting Zhao; Feng Di (Journal of Hazardous Materials, 2025)

Endocrine-disrupting effects of 24 colorants used in food contact materials: In vitro and in silico studies - Guowei Ma; Yiling Cui; Qian Li; Yuting Chen; Peixue Guo; Di Feng; Tingting Zhao (Food and Chemical Toxicology, 2025)

Homozygous deleterious variants in MYCBPAP induce asthenoteratozoospermia involving abnormal acrosome biogenesis, manchette structure and sperm tail assembly in humans and mice - Yiling Zhou; Chaofeng Tu; Charles Coutton; Jianan Tang; Shixiong Tian; Shuyan Tang; Guillaume Martinez; Dapeng Zhou; Célia Tebbakh; Jiaxiong Wang; Raoudha Zouari; Xuehai Zhou; et al. (Science China Life Sciences, 2025)

The Translation Initiation Factor eIF2Bα Regulates Development, Stress Response, Amylase Production, and Kojic Acid Synthesis in the Fungus Aspergillus oryzae - Yiling Liu; Zixin Chen; Chaofeng Chang; Yifen Lin; Guiyi Zheng; Feng Zhang (Current Microbiology, 2025)

A key component Rxt3 in the Rpd3L histone deacetylase complex regulates development, stress tolerance, amylase production and kojic acid synthesis in Aspergillus oryzae - Chaofeng Chang; Herui Wang; Yiling Liu; Yiting Xie; Dingxiang Xue; Feng Zhang (Biotechnology Letters, 2024)

P-phenylenediamine antioxidants and their quinone derivatives: A review of their environmental occurrence, accessibility, potential toxicity, and human exposure - Yuting Liang; Feng Zhu; Jie Li; Xin Wan; Yiling Ge; Geyu Liang; Yonglin Zhou (Science of The Total Environment, 2024)

Phthalate acid esters: A review of aquatic environmental occurrence and their interactions with plants - Jiefeng Liang; Xiaomeng Ji; Xiaoxia Feng; Pinjie Su; Wenzhuo Xu; Qingzhe Zhang; Zhihua Ren; Yiling Li; Qingqing Zhu; Guangbo Qu; Runzeng Liu (Journal of Hazardous Materials, 2024)

Bufogarlides A-C, three new bufadienolides with Δ 14,15 double bond from the skins of Bufo bufo gargarizans - Lingjie Meng; Qinghong Kong; Jianxun Xie; Feng Pan; Keyu Lu; Sanhua Li; Yiling Li; Di Zhang; Yun Liu (Natural Product Research, 2024)

Cuprotosis clusters predict prognosis and immunotherapy response in low-grade glioma - Wenjun Zhu; Ziqi Chen; Min Fu; Qianxia Li; Xin Chen; Xiaoyu Li; Na Luo; Wenhua Tang; Feng Yang; Yiling Zhang; Yuanyuan Zhang; Xiaohong Peng; et al. (Apoptosis, 2024)
Cuprotosis, an emerging mode of cell death, has recently caught the attention of researchers worldwide. However, its impact on low-grade glioma (LGG) patients has not been fully explored. To gain a deeper insight into the relationship between cuprotosis and LGG patients’ prognosis, we conducted this study in which LGG patients were divided into two clusters based on the expression of 18 cuprotosis-related genes. We found that LGG patients in cluster A had better prognosis than those in cluster B. The two clusters also differed in terms of immune cell infiltration and biological functions. Moreover, we identified differentially expressed genes (DEGs) between the two clusters and developed a cuprotosis-related prognostic signature through the least absolute shrinkage and selection operator (LASSO) analysis in the TCGA training cohort. This signature divided LGG patients into high- and low-risk groups, with the high-risk group having significantly shorter overall survival (OS) time than the low-risk group. Its predictive reliability for prognosis in LGG patients was confirmed by the TCGA internal validation cohort, CGGA325 cohort and CGGA693 cohort. Additionally, a nomogram was used to predict the 1-, 3-, and 5-year OS rates of each patient. The analysis of immune checkpoints and tumor mutation burden (TMB) has revealed that individuals belonging to high-risk groups have a greater chance of benefiting from immunotherapy. Functional experiments confirmed that interfering with the signature gene TNFRSF11B inhibited LGG cell proliferation and migration. Overall, this study shed light on the importance of cuprotosis in LGG patient prognosis. The cuprotosis-related prognostic signature is a reliable predictor for patient outcomes and immunotherapeutic response and can help to develop new therapies for LGG.

Amine-functionalized cotton for the treatment of oily wastewater - Yiling Ao; Ji'an He; Keming Chen; Mingzhao Zhu; Fan Ye; Liwei Shen; Ying Yang; Xuening Feng; Zejun Zhang; Yuqi Tang; Yuanzhu Mi (Environmental Research, 2023)

Effects of dietary adenosine and adenosine 5′-monophosphate supplementation on carcass characteristics, meat quality, and lipid metabolism in adipose tissues of finishing pigs - Sujuan Rao; Zhijuan Cui; Longmiao Zhang; Shuo Ma; Shuangbo Huang; Li Feng; Yiling Chen; Jinxi Luo; Jinfeng Li; Shiyu Qian; Hanting Liu; Yanzhi Liu; et al. (Meat Science, 2023)

The role of N6-methyladenosine methylation in environmental exposure-induced health damage - Yanlu Feng; Tong Liu; Siyi Xu; Yiyi Ren; Yiling Ge; Lihong Yin; Yuepu Pu; Geyu Liang (Environmental Science and Pollution Research, 2022)

Use of DNA nanosensors based on upconverting nanoparticles for detection of Nosema bombycis by fluorescence resonance energy transfer - Ping He; Hongli Chen; Jiancheng Sun; Qiang Wang; Xudong Tang; Yiling Zhang; Feng Zhu; Zhongyuan Shen (Folia Microbiologica, 2022)

Florescence Imaging Lung Cancer with a Small Molecule MHI-148 - Xiaotian Xia; Yongkang Gai; Hongyan Feng; Chunxia Qin; Dongfeng Pan; Yiling Song; Yongxue Zhang; Xiaoli Lan (Journal of Fluorescence, 2020)

Immunization with an adenovirus-vectored TB vaccine containing Ag85A-Mtb32 effectively alleviates allergic asthma - Yiling Zhang; Ying Feng; Liang Li; Xianmiao Ye; Jinlin Wang; Qian Wang; Pingchao Li; Na Li; Xuehua Zheng; Xiang Gao; Chufang Li; Feng Li; et al. (Journal of Molecular Medicine, 2018)

Trap Induction and Trapping in Eight Nematode-trapping Fungi (Orbiliaceae) as Affected by Juvenile Stage of Caenorhabditis elegans - Hongyan Xie; F. M. Aminuzzaman; Lingling Xu; Yiling Lai; Feng Li; Xingzhong Liu (Mycopathologia, 2010)